2014
DOI: 10.1027/1618-3169/a000238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative Stimulus (In)Congruency Impacts Performance in an Unrelated Task

Abstract: In two experiments, we assessed evaluative priming effects in a task that was unrelated to the congruent or incongruent stimulus pairs. In each trial, participants saw two valent (positive or negative) pictures that formed evaluatively congruent or incongruent stimulus pairs and a letter that was superimposed on the second picture. Different from typical evaluative priming studies, participants were not required to respond to the second of the valent stimuli, but asked to categorize the letter that was superim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
(40 reference statements)
3
10
0
Order By: Relevance
“…The fact that an evaluative priming effect can be obtained under these conditions thus confirms the classic hypothesis that automatic stimulus evaluation is not contingent upon the presence of an explicit evaluative processing goal (e.g., Bargh et al, 1996;, even though the effect seems to dissipate quickly over time (i.e., the effect was reliable only in the first block of trials). At first sight, however, this conclusion may seem incompatible with the observation that the evaluative priming effect typically fails to replicate in the absence of dimensional overlap between the prime set and the target set unless the experimental conditions encourage participants to assign selective attention to the evaluative stimulus dimension (e.g., Everaert et al, 2011;Gast et al, 2014;Spruyt et al, 2009;. To reconcile these findings, we argue that selective attention for the evaluative stimulus dimension may be a prerequisite for obtaining the evaluative priming effect only if the primed stimuli under investigation have no particular relevance for the participants.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The fact that an evaluative priming effect can be obtained under these conditions thus confirms the classic hypothesis that automatic stimulus evaluation is not contingent upon the presence of an explicit evaluative processing goal (e.g., Bargh et al, 1996;, even though the effect seems to dissipate quickly over time (i.e., the effect was reliable only in the first block of trials). At first sight, however, this conclusion may seem incompatible with the observation that the evaluative priming effect typically fails to replicate in the absence of dimensional overlap between the prime set and the target set unless the experimental conditions encourage participants to assign selective attention to the evaluative stimulus dimension (e.g., Everaert et al, 2011;Gast et al, 2014;Spruyt et al, 2009;. To reconcile these findings, we argue that selective attention for the evaluative stimulus dimension may be a prerequisite for obtaining the evaluative priming effect only if the primed stimuli under investigation have no particular relevance for the participants.…”
Section: Discussionmentioning
confidence: 93%
“…Taken together, this line of research strongly suggests that processes other than direct response facilitation and/or interference can contribute to the emergence of the evaluative priming effect. As an example of such an alternative explanation, it has been suggested that the perceptual encoding of a target stimulus is more cognitively demanding (and therefore more time-consuming) if it is preceded by an incongruent prime stimulus (Gast et al, 2014), at least under conditions that promote selective attention for the evaluative stimulus dimension. Further research would be needed, however, to firmly substantiate this idea.…”
Section: Discussionmentioning
confidence: 99%
“…It must be emphasized, however, that the present findings are insufficient to draw strong conclusions concerning the precise nature of the processes that are responsible for the translation of the prime-evaluation process into an observable evaluative priming effect [ 21 ]. As already pointed out by Spruyt [ 4 ], (at least) three mechanisms may or may not be at play in the valent/non-valent categorization task: encoding facilitation [ 12 ], automatic affective matching, [ 9 ], and/or affective-motivational conflict reduction [ 34 ]. So, despite the fact that direct response activation can be ruled out as an underlying mechanism of the evaluative priming effect in the valent/non-valent categorization task, it remains unclear to what extent other mechanisms contribute to the effect.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently summarized empirical work, however, suggesting that the contribution of linguistic factors is probably quite small (Klauer et al, in press). In sum, more research is needed to further examine the extent to which evaluative information can impact early encoding processes, preferably using a diverse set of paradigms that (Gast et al, 2014;Spruyt, 2014;Spruyt and Tibboel, 2015;Werner & Rothermund, 2013; also see online supplement).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bargh et al (1996) suggested that the mere perception of a prime stimulus is sufficient to activate all other concepts of the same valence in memory. Others, however, have argued that evaluative incongruency of prime and target results in an internal conflict that consumes cognitive resources (Gast, Werner, Heitmann, Spruyt, & Rothermund, 2014;Hermans, Van den Broeck, & Eelen, 1998), leading to depressed task performance. Finally, some scholars have questioned the assumption that evaluative information can influence subsequent early-stage encoding processes (e.g., Klauer, Roßnagel, & Musch, 1997).…”
mentioning
confidence: 99%